2017
DOI: 10.3233/jad-170317
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Amnesia for Episodic and Semantic Memories in Amnestic Mild Cognitive Impairment

Abstract: Abstract. Retrograde amnesia (RA), which includes loss of memory for past personal events (autobiographical RA) and for acquired knowledge (semantic RA), has been largely documented in patients with amnestic mild cognitive impairment (aMCI). However, previous studies have produced controversial results particularly concerning the temporal extent of memory impairment. Here we investigated whether, with the onset of hippocampal pathology, age of memory acquisition and retrieval frequency play different roles in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
(80 reference statements)
0
7
0
Order By: Relevance
“…Period A: 1969–78; Period B: 1997–2001; Period C: 2009–13) was assessed using two different procedures, that is, free recall and recognition tests. In order to potentially control for difference in media exposure, the six famous events were selected from a large set of 50 public events because they were judged as widely‐known and frequently‐retrieved by at least 70% (range 70%–85%) of the experimental sample in a previous study (De Simone, Fadda, et al, 2017). In the free recall procedure, the participants were asked to try to remember as much information as possible about the public events without any cue or suggestion (only specific prompts were allowed in order to elicit as much detail as possible, that is “What happened?” “Where and when did the event take place?” “Who was involved?”).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Period A: 1969–78; Period B: 1997–2001; Period C: 2009–13) was assessed using two different procedures, that is, free recall and recognition tests. In order to potentially control for difference in media exposure, the six famous events were selected from a large set of 50 public events because they were judged as widely‐known and frequently‐retrieved by at least 70% (range 70%–85%) of the experimental sample in a previous study (De Simone, Fadda, et al, 2017). In the free recall procedure, the participants were asked to try to remember as much information as possible about the public events without any cue or suggestion (only specific prompts were allowed in order to elicit as much detail as possible, that is “What happened?” “Where and when did the event take place?” “Who was involved?”).…”
Section: Methodsmentioning
confidence: 99%
“…Retrograde memory impairments have been widely documented in patients with amnestic mild cognitive impairment (a‐MCI) and Alzheimer's disease (AD) from the earliest stages of the disease (De Simone et al, 2016; De Simone, Fadda, et al, 2017; Leyhe et al, 2009; Serra et al, 2020, 2022). However, the nature of this memory impairment in relation to the underpinning cognitive processes responsible for the failure to remember remote information has not yet been extensively explored.…”
Section: Introductionmentioning
confidence: 99%
“…The situation is more controversial for what concerns the semantic component. Fourteen studies out of twenty-one have studied this aspect, while seven articles [26,32,[34][35][36][37][38] focused only on the episodic component. Among the 14 articles that analyzed autobiographical semantic memory, 4 of them [21,24,29,33] have not found any significant differences in semantic memory scores between patients with MCI and healthy controls.…”
Section: Episodic and Semantic Autobiographical Memorymentioning
confidence: 99%
“…In our review, 13 studies [16,[21][22][23][24][25][26]28,31,34,35,37,39] examined the temporal gradient in the recall of episodic autobiographical memories in patients with MCI. Three articles [21][22][23] did not find significant differences in time-period performance.…”
Section: Temporal Gradientmentioning
confidence: 99%
“…More recently, a study assessing the famous people knowledge in AD and aMCI patients found evidence of temporal gradient for enduring famous people but not for transient famous people (Benoit et al, 2017). De Simone et al, (2017) investigated a group of aMCI patients and found evidence for a strong temporal gradient in the recall of public events as well as of personal incidents that were related to the occurrence of public events. In a second study, which aimed at assessing the contribution of storage and retrieval processes on the pattern of retrograde memory impairment, the same group reported the presence of temporal gradient in the recall performance of both aMCI and AD patients (De Simone et al, 2020).…”
mentioning
confidence: 99%